Understanding Metabolized Violence: Intimate and Socio-affective Ties of Terror in Basque Writer Edurne Portela's El eco de los disparos (2016) and Mejor la ausencia (2017). Issue 2 (3rd April 2022) - Martín, Annabel
Abstract: This essay studies the writing of Basque author Edurne Portela (1974) and its special sensitivity toward the micropolitics of violence. Rejecting Basque society's immunity to the tragedy of ETA violence, ignoring the call to "turn the page" after ETA's permanent disarmament (2011) and disappearance (2018), Portela's fiction betrays Basque and Spanish society's ignorance and insensitivity toward the ways trauma infiltrates the fabric of societal, familial, and interpersonal relationships. Instead of promoting a lazy and cowardly amnesiac turn for post ETA society, Portela prefers to look straight into the eyes of a community known for turning its back on what philosopher Reyes Mate terms a society's "deber de memoria" or responsibility to remember. Portela's fiction, essay, and autobiographical writing do just that. On the one hand, they confront readers with the uncomfortable weight of the traumatic experiences unjustly suffered by members of Basque society, injuries that undermine its democratic fabric; on the other, and even more importantly, Portela looks inward, and her fictional universe begs readers to question how this indifference also mutilates the affective life of characters who either look the other way or find it easy to participate and justify the logic of terror and violence.